Importance of Organized Energy Efficiency Introduction and Improvement in PE EPS - Nikolic, Aleksandar B; Đorđević, Vladimir (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
The energy management system (EnMS) introduction into companies that are significant energy consumers has been initiated after adoption of the Law of efficient energy usage. Due to the fact that sectors for production, transmission and distribution of electrical and heat energy are also implied by this law, it is clear that PE EPS is also obligated to implement EnMS and to carry out the requirements defined by legislation. In this paper, the results of first-phase introduction of the system for supervision and improvement of energy efficiency in PE EPS in production of coal, and production and distribution of electrical and heat energy, are given. Recommended measures for energy efficiency improvement with stress on larger energy, financial savings and a lower rate of investment return are emphasised. Such systematic measures should also serve as a good basis for further stages of energy management introduction and implementation.